Cultural effects, working decisions and values in perspective trust level in the ministry of education and culture / Faroman Syarief, Kurniawan Prambudi Utomo, Supriyanto and Fahmi Kamal - Syarief, Faroman; Prambudi Utomo, Kurniawan; -, Supriyanto; Kama, Fahmi (UiTM Cawangan Johor, 2019)
Culture, propriety and organizational values are part of important human resources in the work process in every aspect of activities, this will bring the level of public trust as stakeholders holding people's sovereignty to choose democratic leaders to improve better services, therefore the ministry must make policies and rules that are able to accommodate employees to be motivated to work well. This research method uses a quantitative approach using the personally administered questioner method, which is direct questionnaire distribution to face-to-face respondents because among independent variables with dependent variables there is an influencing mediation, while the purpose of this study is to explain the relationship of causal effects of several variables. The results showed that the organizational culture variable showed a number of 0.088 (8%), while the work propriety variable showed a number of 0.169 (1.6%), and the organizational value variable showed a number of 0.301 (30%), so that the variable significantly affected the level public trust is 23.47 and the equation model is as follows the multiple regression equation that describes the relationship of the influence of culture organization, work propriety and organizational value to the level of organization as follows Y = 23.47 + 0.088X1 + 0.169X2 + 0.301X3 + e.